USING ANTCONC: TO ANALYZE THE VARIATION OF WORDS IN WILLIAM SHAKESPEARE NOVEL’S (HAMLET, ROMEO AND JULIET, AND THE TEMPEST) - Setiawan, Laode; Armanda, Muhammad Laudy (Faculty of Education and Teachers Training, 2023)
Corpus linguistics studies the use of real-life language based on a text corpus by using quantitative and qualitative text analysis techniques. This study investigated the variation of words and calculated word-class occurrences in William Shakespeare Novel's (Hamlet, Romeo and Juliet, and The Tempest). Variation of words is the total percentage of word variations used in a text that can determine the richness of the writer's word variations. This study employed a descriptive qualitative method and corpora analysis approach with data obtained quantitatively. AntConc was used to count and list all the words used in each novel based on the context. These words were then sorted based on their word classes to arrive at a valid conclusion. In analyzing the corpora using AntConc, the researcher presents data on the percentage of word variations and word-class, which provide the frequencies content words and function words. The findings of this result have three points. First, the researchers imply that William Shakespeare Novel's variation of words was increased each year. Second, all of these novels’ most frequent content words are nouns, which are the characters' names in the novel. These novels have the same form in providing the stories within a direct conversation. And third, the novels have a difference in the most frequent function words.